2020
DOI: 10.1177/1757177420948580
|View full text |Cite
|
Sign up to set email alerts
|

DropSafe safety pen needle helps to prevent accidental needlesticks after injections: results of a simulated clinical study

Abstract: Background: Most needlestick injuries (NSIs) result from unsafe needle devices. DropSafe safety pen needle (SPN) was designed to help prevent such injuries before, during and after use through a built-in sharps injury prevention feature (SIPF). Methods: A two-phase study was undertaken. For the pilot study, five non-healthcare users (NHCUs) performed evaluations. For the validation study, 30 evaluators comprising 10 healthcare professionals (HCPs) and 20 NHCUs performed evaluations. The aim of the study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…Likewise, Veronesi et al [24], highlighted that the compatibility and simplicity of SPN contributed to a high satisfaction (85%) among the general hospital nurses in northern Italy. Our findings also run in parallel with a recent report by Malinowski et al, in which the SPN was associated with ease-of-use, user satisfaction, and a low incidence of needlestick injuries [11].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Likewise, Veronesi et al [24], highlighted that the compatibility and simplicity of SPN contributed to a high satisfaction (85%) among the general hospital nurses in northern Italy. Our findings also run in parallel with a recent report by Malinowski et al, in which the SPN was associated with ease-of-use, user satisfaction, and a low incidence of needlestick injuries [11].…”
Section: Discussionsupporting
confidence: 91%
“…Safety pen needles (SPN), which were primarily introduced for hospital settings, can reduce accidental puncture risk through a retractable shield that automatically lockouts the needle after injection [10]. Recent reports highlighted that SPN was associated with ease-of-use, users' satisfaction, and a low incidence of needlestick injuries [11]. Moreover, it was shown that the use of SPN needed no additional education for the patients who self-administrated their insulin [12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the incidence of needlestick injury among nurses in China was 57.3% [ 2 ]; the incidence among intern nurses is even higher, about 60.8% [ 3 ]. Safety needles can be selected to effectively avoid such accidents [ 4 , 5 ]. Traditional blood sampling devices need to press open the catheter valve inward to facilitate inserting a syringe into the valve in order to draw blood.…”
Section: Introductionmentioning
confidence: 99%